Continuity and Discontinuity in Cultural Conditioning Ruth Benedict - M. Refki Yansyah (Kamara Journal, 2024)
In our culture, the human growth cycle is a constant, from vulnerable infants to adults. Ruth Benedict underscores the physiological contrast between the two, as well as the roles that change over time. While these facts of nature underlie discussions of humans, the anthropologist's role is to analyze the interaction between "nature" and human behavior, and how culture influences it. In this context, Benedict highlights the concepts of continuity and discontinuity, describing variations in child training in different cultures and differences in roles between children and adults. She points out that although physiological differences exist, the process of transitioning from child to adult varies significantly between societies. In her paper, Benedict analyzes three contracts that are prominent in culture, namely non-responsive responsible status, compliance dominance, and limited sexual roles. This research helps to understand how culture plays an important role in the formation of the human life cycle, highlighting the continuities and discontinuities that exist across different cultures.